Onychophoran Hox genes and the evolution of arthropod Hox gene expression - Janssen, Ralf; Eriksson, Bo Joakim; Tait, Noel N; Budd, Graham E (Frontiers in zoology, 2014)
INTRODUCTION: Onychophora is a relatively small phylum within Ecdysozoa, and is considered to be the sister group to Arthropoda. Compared to the arthropods, that have radiated into countless divergent forms, the onychophoran body plan is overall comparably simple and does not display much in-phylum variation. An important component of arthropod morphological diversity consists of variation of tagmosis, i.e. the grouping of segments into functional units (tagmata), and this in turn is correlated with differences in expression patterns of the Hox genes. How these genes are expressed in the simpler onychophorans, the subject of this paper, would therefore be of interest in understanding their subsequent evolution in the arthropods, especially if an argument can be made for the onychophoran system broadly reflecting the ancestral state in the arthropods. RESULTS: The sequences and embryonic expression patterns of the complete set of ten Hox genes of an onychophoran (Euperipatoides kanangrensis) are described for the first time. We find that they are all expressed in characteristic patterns that suggest a function as classical Hox genes. The onychophoran Hox genes obey spatial colinearity, and with the exception of Ultrabithorax (Ubx), they all have different and distinct anterior expression borders. Notably, Ubx transcripts form a posterior to anterior gradient in the onychophoran trunk. Expression of all onychophoran Hox genes extends continuously from their anterior border to the rear end of the embryo. CONCLUSIONS: The spatial expression pattern of the onychophoran Hox genes may contribute to a combinatorial Hox code that is involved in giving each segment its identity. This patterning of segments in the uniform trunk, however, apparently predates the evolution of distinct segmental differences in external morphology seen in arthropods. The gradient-like expression of Ubx may give posterior segments their specific identity, even though they otherwise express the same set of Hox genes. We suggest that the confined domains of Hox gene expression seen in arthropods evolved from an ancestral onychophoran-like Hox gene pattern. Reconstruction of the ancestral arthropod Hox pattern and comparison with the patterns in the different arthropod classes reveals phylogenetic support for Mandibulata and Tetraconata, but not Myriochelata and Atelocerata.